GROUNDWATER SUITABILITY FOR DRINKING PURPOSE IN AURANGABAD AREA, MAHARASHTRA, INDIA: A WATER QUALITY INDEX (WQI) APPROACH - Nisha M. Walde,; Kavita S. Raipurkar,; Kavita S. Raipurkar,; Mahendra G. Thakare, (The Bioscan, 2025)
The depleting groundwater quality poses major risks to human health, ecologies and the environment. This study was an effort to evaluate the potability of subterranean water in Aurangabad area, Maharashtra by the WQImethod, aninclusivetechnique for assessing and detecting the appropriateness of groundwater for human consumption. The total 60 samples of groundwater were collected from different selected locations and a comprehensive examination of groundwater quality was conducted, comprising a range of physical parameters (colour, odour, taste, TDS, turbidity, and EC), chemical parameters (TA, TH and pH) and inorganic parameters(sulfate, chloride, fluoride, nitrate, and iron). The ranged of WQI values obtained from excellent to unfit for drinking. The results showed that only 2% samples showing excellent water quality. The majority of samples that is about 47.5% showed poor to very poor water quality, while 12% samples were estimated unfit for drinking. The results underlined the need for effective groundwater management policies, including monitoring, protection, and justifiable use practices, to protect this crucial resource and ensure the health and well-being of societiesdependent on groundwater.